Immunological Relationships of Reverse Transcriptases from Ribonucleic Acid Tumor Viruses - Parks, Wade P. (1972)
Antiserum to partially purified reverse transcriptase from the Schmidt-Ruppin strain of Rous sarcoma virus has been prepared and characterized. Antibody to the avian polymerase inhibited the reverse transcriptase activity of avian C-type viruses but had no effect on the polymerase activity from C-type viruses of other classes. The known mammalian C-type viral polymerases were significantly inhibited only by the antiserum to murine C-type viral polymerases; reverse transcriptases from four other mammalian viruses were immunologically distinct from both avian and mammalian C-type viral polymerases. Partially purified murine leukemia viral DNA polymerase activity was comparably reduced by specific antibody regardless of the template used for enzyme detection.